Strategies for enhancing the understanding of Islam in the media - Yousif, Ahmad (2010)
During the last two decades, the world witnessed a meteoric rise in the role played by the media for influencing human perceptions of other people, places and things. This tremendous influence has had both beneficial and detrimental consequences for individuals and communities across the globe. On one hand, the media has proven to be a valuable source of information on a wide variety of subject matters, including news, education, entertainment, health, sport and finance, just to name a few. In addition, its very nature has enabled it to cross national, racial, ethnic, socio-economic, and geographical boundaries. On the other hand, the media has frequently become an instrument of cultural domination and prejudice against those who do not accept the contemporary geo-political power structure. Muslims have experienced first-hand the harmful impact of the global media and its ability to negatively manipulate public opinion. This continuous negative portrayal of Muslims by the media has led many Muslims to perceive it as a conspirator against them. How has such a state of affairs come about? Why is Islam so misunderstood in the global media and more importantly how can this situation be remedied? This paper will examine some of the reasons for the media’s misunderstanding and biased portrayal of Islam, firstly in the Western world and secondly in the Muslim world. Subsequently, it will examine and propose various strategies for enhancing the Western and Muslim media’s understanding of Islam at both domestic and international levels.